2014
DOI: 10.3109/0886022x.2014.967699
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor induces tubular epithelial to mesenchymal transition through the activation of canonical Wnt signalingin vitro

Abstract: Background: Overwhelming evidences suggest epithelial to mesenchymal transition (EMT) of tubular epithelial cells contributes to renal fibrosis of chronic kidney disease (CKD). Connective tissue growth factor (CTGF) plays an important role in the pathogenesis of EMT. However, the molecular mechanisms that regulate cell behaviors are not clear. Objective: The purpose of this study was to investigate whether CTGF induces EMT via activation of canonical Wnt signaling in renal tubular epithelial cells. Methods: Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Similar situations occurred with IL7R vs IL1R, and THBS1 vs THBD, although the pattern of the joint involvement of the overall IL, IGF, and TGFβ families is in agreement with their cooperative role as EMT inducers ( 68 ). The considerable upregulation by ethanol of CTGF is also in agreement with its well known role in EMT ( 69 ), but the concerted upregulation of IGFBPs 2, 3 and 4 is more intriguing, considering the paucity of studies and some conflicting evidence for their pro- versus anti-EMT effects ( 70 72 ). The upregulation of IGFR2 is in agreement with the higher levels observed in breast cancer tissue ( 73 ).…”
Section: Discussionsupporting
confidence: 54%
“…Similar situations occurred with IL7R vs IL1R, and THBS1 vs THBD, although the pattern of the joint involvement of the overall IL, IGF, and TGFβ families is in agreement with their cooperative role as EMT inducers ( 68 ). The considerable upregulation by ethanol of CTGF is also in agreement with its well known role in EMT ( 69 ), but the concerted upregulation of IGFBPs 2, 3 and 4 is more intriguing, considering the paucity of studies and some conflicting evidence for their pro- versus anti-EMT effects ( 70 72 ). The upregulation of IGFR2 is in agreement with the higher levels observed in breast cancer tissue ( 73 ).…”
Section: Discussionsupporting
confidence: 54%
“…This point warrants further investigation. Furthermore, recent studies have reported that CTGF itself induces EMT in renal cells (46,47). If this is also the case in retinal cells, we can assume that CTGF and Snail form a positive loop, resulting in a vicious circle of the development of vitreoretinal disorders.…”
Section: Discussionmentioning
confidence: 91%
“…Hydrogen sulfide inhibits TGF-β1-induced EMT via Wnt/β-catenin pathway ( Guo et al, 2016 ). CTGF induces tubular EMT through the activation of canonical Wnt signaling ( Yang et al, 2015 ). Chronic cadmium exposure induces activation of the Wnt pathway and upregulation of EMT markers in mouse kidney ( Chakraborty et al, 2010 ).…”
Section: New Signals That Mediate Pemt and Subsequent Renal Fibroblasmentioning
confidence: 99%